The Useful Presence of the Past: on the Years of the «Revolución Libertadora» in a City of the Interior of Argentina (1955-1958) - Escudero, Eduardo Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article documents and interprets the uses of the past unfolded during the dictatorship established from 1955 in Argentina, after the fall of Peronism. The analytical perspective involves observing the way in which the past ended up being a key resource in the legitimation of a new political order and the characterization of enemies, in order to offer new interpretations of history, rescuing, as well as resignifying, the heroes of the national past. The study is oriented from a speciically local perspective, investigating the discourses, practices and representations of the past that can be found in the city of Río Cuarto, Córdoba, Argentina during the political process that sought to “deperonize” the public space and restore the liberal matrix of the country´s political and historical culture. The methodology involved the exegesis of journalistic primary resources, qualitatively characterizing the discursivity of the time period. As a result of the analytic study of the uses of the past found, it is possible to observe how the different key agents of ríocuartense politics, culture and education, established a series of cognitive, argumentative and symbolic uses of the past, in order to accomplish the task of sculpting social memory for the new political order: attemping to reestablish the memory of the liberal nation, in pedagogical and intense opposition to Peronism.